2020
DOI: 10.1111/jog.14497
|View full text |Cite
|
Sign up to set email alerts
|

How could we suspect life‐threatening perinatal group A streptococcal infection?

Abstract: Aim: Perinatal group A streptococcal infection is a rare but life-threatening condition. Few reports have focused on its clinical characteristics and how to prevent deterioration. We report our experience with two antenatal fatal cases and reviewed 96 cases in the literature to assess the clinical characteristics of group A streptococcal infection. Methods: English-language clinical reports of antenatal and postnatal group A streptococcal infection in 1974-2019 were retrieved and examined. Relationships betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Their study found a link between antenatal GAS infection and age ≤19 or ≥35 years old, Caesarean section, sore throat as an initial symptom, positive throat culture, maternal death, and fetal death. Postnatal infections are significantly associated with an onset during hospitalization, abnormal vaginal discharge, and surgical intervention ( 11 ). Caesarean section had been performed three months prior to the onset of infection in the present case, implying a possible association.…”
Section: Discussionmentioning
confidence: 99%
“…Their study found a link between antenatal GAS infection and age ≤19 or ≥35 years old, Caesarean section, sore throat as an initial symptom, positive throat culture, maternal death, and fetal death. Postnatal infections are significantly associated with an onset during hospitalization, abnormal vaginal discharge, and surgical intervention ( 11 ). Caesarean section had been performed three months prior to the onset of infection in the present case, implying a possible association.…”
Section: Discussionmentioning
confidence: 99%